The productivity of indigenous goats under traditional management in Swaziland - Lebbie, S.H.B.; Manzini, A.T. (1989)
Results of a 24 month study of traditional goat production in Swaziland are reported. Females greatly outnumbered males in the flocks. Females kidded first at 301±55 days, kidding interval was 265±100 days, litter size was 1.18±0.29 and kids born per doe per year was 1.61. Birth weight was 1.9 ±0.14kg and growth to 3 month averaged 68.2g/d. Mortality was 30% over the study period and offtake was 17%: home consumption was the largest component of offtake and deaths were much higher in kids than in adults.